Analysis of service quality and connectivity to the effectiveness of commuter line train passengers at Soekarno-Hatta Airport (Basoetta) - Gina Pebriana Zulkarnain; Banun Erlin; Rr.Endang Wahyuni; Masjraul Hidajat (Green Publisher, 2025)
The purpose of this study was to determine the effect of service quality and connectivity on the effectiveness of Soekarno-Hatta airport commuter line train passengers. The population in this study were all passengers of the Soekarno-Hatta Airport Commuter Line (Basoetta) train who used the train service. The research employed a quantitative methodology, utilizing data analysis techniques such as validity testing, reliability testing, multiple linear regression testing, multiple correlation coefficient testing, multiple determination coefficient testing, partial T testing, simultaneous F testing, and assessment of classical assumptions, including multicollinearity testing. The data analysis in this study reveals that both service quality and connectivity have a positive and statistically significant impact, either individually or together. This implies that passengers are content with the level of service quality and connection provided by the Soekarno-Hatta Airport Commuter Line (Basoetta).